2004
DOI: 10.1080/1355785042000285366
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, education, and the cortisol response to awakening: A preliminary investigation

Abstract: These preliminary findings demonstrate significant ethnic and education-related differences in awakening cortisol secretion responses. Our data highlight the importance of considering ethnicity and the moderating effects of social class when examining the associations among social contextual factors and cortisol secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 0 publications
3
46
1
Order By: Relevance
“…These studies show that African Americans mount higher ACTH but similar cortisol responses to an exercise test or following corticotropin-releasing factor administration compared to Caucasians. However, in another study, salivary cortisol response to awakening was heightened in Caucasians with higher education compared to lower educated Caucasians and all African-American participants (Bennett et al, 2004). In our study, African Americans had minimal but significant cortisol responses to the TSST.…”
Section: Discussioncontrasting
confidence: 64%
“…These studies show that African Americans mount higher ACTH but similar cortisol responses to an exercise test or following corticotropin-releasing factor administration compared to Caucasians. However, in another study, salivary cortisol response to awakening was heightened in Caucasians with higher education compared to lower educated Caucasians and all African-American participants (Bennett et al, 2004). In our study, African Americans had minimal but significant cortisol responses to the TSST.…”
Section: Discussioncontrasting
confidence: 64%
“…Also, given the difference in ethnic distribution between groups, the possibility of other, more ethnicity-specific polymorphisms that influence HPA axis function cannot be ruled out. The direct influence of ethnicity on basal and stress-induced cortisol levels has been studied with conflicting results, which indicates that ethnicity alone may not influence cortisol; however, disparities in socioeconomic factors, which are often along ethnic lines may explain these conflicting results (eg Bennett et al, 2004;Masi et al, 2004). This study was not large enough to control for demographic factors such as socioeconomic status and education.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, lower levels of morning cortisol have been described among blacks compared with whites, while accounting for perceived stress (Bennett et al, 2004). There is also evidence that race and ethnicity influences the diurnal variations in cortisol (Cohen et al, 2006;Gallagher-Thompson et al, 2006;McCallum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cortisol levels upon waking have been shown to be higher among highereducated whites compared with blacks and lower educated whites (Bennett et al, 2004). Another study has suggested that blacks experience a less steep decline in cortisol during the course of the day, even after accounting for differences in socioeconomic status (Cohen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%